The Implementation of the Lalaran Method in Enhancing Students’ Memorization Skills at Madrasah Diniyah Darut Tauhid Brongkal - Alfatun Nisak; Siti Lailatul Qomariah; Lailatul Mufarrohah (Universitas PGRI Sumatera Barat, 2026)
This study aims to analyze the implementation of the lalaran method in enhancing the memorization skills of students at Madrasah Diniyah Darut Tauhid Brongkal. The background highlights the significance of memorization in Islamic education, where students are trained to memorize religious texts from an early age. The lalaran method, which involves repetitive oral recitation of texts, is a traditional approach used in madrasah to strengthen students' auditory and verbal memory. This qualitative descriptive research employs interviews, observations, and documentation to gather data on the lalaran practice and its impact on students' memorization abilities. Findings indicate that the lalaran method is conducted regularly and structured, fostering a collective learning environment that enhances memorization and builds discipline among students. The study concludes that while the lalaran method effectively improves memorization, challenges such as physical fatigue and lack of motivation among students need to be addressed. Recommendations include varying the lalaran format and integrating meaning comprehension to enrich the learning experience.